Theory of Planned Behavior: The Effect of Financial Literacy and Risk Tolerance on Investment Intention - Rizani, Anisa Aulia; Hendrawaty, Ernie; Puspitasari D., Nindytia (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This research aims to analyze how factors such as attitude, subjective norms, perceived behavioral control, financial literacy, and risk tolerance influence the investment intentions of university students. By focusing on these variables, the study seeks to provide a comprehensive understanding of the determinants of investment behaviors among this demographic. Design/methodology/approach: Utilizing the Theory of Planned Behavior as a guiding framework, the study employed a quantitative research approach. A survey, comprising structured questionnaires, was administered to a sample of students currently enrolled at the University of Lampung. The responses were then analyzed using multiple linear regression to identify significant predictors of investment intentions. Research Findings: The analysis revealed that attitude and perceived behavioral control are significant predictors of investment intention among University of Lampung students. Contrary to expectations, subjective norms, financial literacy, and individual risk tolerance did not show a significant direct influence on the investment intentions of the participants. Theoretical Contribution/Originality: This study contributes to the body of knowledge in financial behavior theory by contextualizing the Theory of Planned Behavior in the realm of student investment intentions. It offers original insights into the relative importance of various psychological and educational factors in shaping investment behavior among university students, a demographic that is often underrepresented in financial behavior research.